Corporate Yield Spreads: Default Risk or Liquidity? New Evidence from the Credit Default Swap Market - LONGSTAFF, FRANCIS A.; MITHAL, SANJAY; NEIS, ERIC (Journal of Finance, 2005)
ABSTRACT We use the information in credit default swaps to obtain direct measures of the size of the default and nondefault components in corporate spreads. We find that the majority of the corporate spread is due to default risk. This result holds for all rating categories and is robust to the definition of the riskless curve. We also find that the nondefault component is time varying and strongly related to measures of bond‐specific illiquidity as well as to macroeconomic measures of bond market liquidity.